Inside Microfinance Matrix: Microfinance Institutions’ Characteristics and Women Credit Access - Jasmi, Zarith Sofia; Hassan, Nurfarhana (International Journal of Economics and Financial Issues, 2024)
This study aims to explore the role of Microfinance Institutions’ (MFIs) organisational characteristics including ownership structure, target market, and institutional size, in shaping the lending pattern in reaching women entrepreneurs. This study employs Ordinary Least Square and Fractional Logit regression using STATA on pooled panel data of 2,330 MFIs across 116 countries. A fuzzy algorithm and Principal Component Analysis are applied to verify the consistency of the results. Findings suggest larger MFIs demonstrate greater inclusivity towards women, attributed to their extensive resources and institutional capabilities. Similarly, MFIs targeting affluent clients exhibit a higher likelihood of catering to the financial needs of women. Non-government organisations (NGOs) emerge as key drivers of women credit access, consistently prioritizing women entrepreneurs through targeted interventions. This study contributes to theoretical implications of the interplay between institutional ownership and goals related to social welfare. This finding also expands microfinance literature by emphasising how ownership influences the strategic orientation of MFIs. This study holds significance for financial regulators, and policymakers to utilise this study as a framework to evaluate the interplay between organisational scale, financial sustainability, and the fulfilment of social objectives within the microfinance sector.